Peningkatan Kadar Dissolved Oxygen pada Area Tambak Mengggunakan Windmill Aerator Tipe Savonius 4 Blade - Darwin Harun; Syarizal Fonna; Ika Wahyuni (Jurnal Teknik Mesin Unsyiah, 2019)
The aeration process is a method  to increase the dissolved oxygen levels in the water environment. In the pond area has a minimum requirement of dissolved oxygen content in the water so that fish can live and develop. The minimum value of dissolved oxygen in the pond area is 4 mg / l, but the higher the level of dissolved oxygen in the pond area, the better the results of the pond. Previous research conducted by Rizki was Analysis of the Potential of Wind Energy for Windmill Aerator Performance of ponds in Alue Kumba in East Aceh Regency, and the results of these studies showed that the wind energy in the Alue Kumba Village had the potential to operate windmill aerators. However, this study has not shown the results of the dissolved oxygen value of the windmill aerator system, therefore this study aims to obtain results and the area that can be reached by a diffuser. The method used is data collection of dissolved oxygen from the diffusser installation with a distance of 1.5 meters and data collection at 3 times, morning, afternoon and evening. Installation of windmill aerator in the morning produces dissolved oxygen value of 7.42 mg / l with a maximum distance of 18 meters, then in the afternoon the oxygen value of 6.23 mg / l with a maximum distance of 15 meters, and for the afternoon conditions the value of dissolved oxygen is 5.16 mg / l with a maximum distance of 16.5 meters. The dissolved oxygen value after the installation of the windmill aerator increased with an average increase of 1-2 mg / l at each measurement point with the highest dissolved oxygen highest value of 7.42 mg / l up from 5.52 mg / l with a maximum distance of 18 meters on the measurement morning. From the results of this study explain that this method can produce a good area of dispersed dissolved oxygen with an average distance of 16.5 meters with a minimum dissolved oxygen condition that is good for fish to develop in the area of the pond